2003
DOI: 10.1242/dev.00626
|View full text |Cite
|
Sign up to set email alerts
|

Targeted expression of the dominant-negative FGFR4a in the eye usingXrx1Aregulatory sequences interferes with normal retinal development

Abstract: Molecular analysis of vertebrate eye development has been hampered by the availability of sequences that can selectively direct gene expression in the developing eye. We report the characterization of the regulatory sequences of the Xenopus laevis Rx1A gene that can direct gene expression in the retinal progenitor cells. We have used these sequences to investigate the role of Fibroblast Growth Factor (FGF) signaling in the development of retinal cell types. FGFs are signaling molecules that are crucial for cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 49 publications
3
44
0
2
Order By: Relevance
“…Previous work demonstrated that the FGF receptor 1 is not required for early Xenopus eye induction or patterning (Kroll and Amaya, 1996), and inactivation of FGF by use of a dominant-negative FGF receptor 1 did not prevent animal blastomeres from contributing to the retina (Moore and Moody, 1999). In contrast, a more recent study in transgenic frogs showed that FGF receptor 4a is required for the correct specification of retinal cell types (Zhang et al, 2003). Also, another group demonstrated that an interaction between FGF and ephrinB1 is required for morphogenetic movements that underlie eye field formation (Moore et al, 2004).…”
Section: Discussionmentioning
confidence: 95%
“…Previous work demonstrated that the FGF receptor 1 is not required for early Xenopus eye induction or patterning (Kroll and Amaya, 1996), and inactivation of FGF by use of a dominant-negative FGF receptor 1 did not prevent animal blastomeres from contributing to the retina (Moore and Moody, 1999). In contrast, a more recent study in transgenic frogs showed that FGF receptor 4a is required for the correct specification of retinal cell types (Zhang et al, 2003). Also, another group demonstrated that an interaction between FGF and ephrinB1 is required for morphogenetic movements that underlie eye field formation (Moore et al, 2004).…”
Section: Discussionmentioning
confidence: 95%
“…The regulatory elements of the Xenopus tropicalis and laevis Rx gene are located in the 5' upstream region of the gene (Hirsch et al, 2002;Zhang et al, 2003). These sequences are able to direct gene expression into the developing eyes and ventral hypothalamus.…”
Section: Regulation Of Rxmentioning
confidence: 99%
“…2 K,L). We used these sequences to investigate the role of FGF signaling mediated by the FGFR-4 in the specification of retinal cell types (Zhang et al, 2003).…”
Section: Regulation Of Rxmentioning
confidence: 99%
“…These genes are involved in the specification of the eye field and the proliferation of retinal progenitor cells. Furthermore, previous studies have shown that the 5Ј-upstream regions of Rax in Xenopus laevis and Xenopus tropicalis contain cis-regulatory elements that direct Rax expression in the developing eye (22,23). However, the trans-acting factors that bind directly to the cis-regulatory elements to regulate Rax expression remain unknown.…”
mentioning
confidence: 99%